Female directors' monitoring and earnings quality: the moderating effect of political connections and family ownership. Issue 5 (21st October 2021) - Tee, Chwee Ming; Kasipillai, Jeyapalan
Abstract : Purpose: This study aims to examine whether the monitoring effectiveness of female directors in corporate boards is moderated by political connections and family ownership. Design/methodology/approach: This study employs a Malaysian dataset of listed firms from 2005 to 2015. The ordinary least squares model (OLS) is used to test all the research questions. Findings: The authors find that female directors' monitoring is associated with higher earnings quality. This implies effective monitoring by female board directors. However, the monitoring effectiveness by female directors is attenuated by political connections; consistent with the argument that politically connected firms (PCFs) are plagued by severe agency problems. On the other hand, the association between female directors and higher earnings quality is strengthened by family ownership, indicating less severe type 1 agency problem. Originality/value: This study is the first to show that the monitoring capability of female board directors is significantly influenced by a country's institutional setting. Although prior studies find that higher proportion of female directors is associated with higher earnings quality; the findings suggest that institutional setting such as political connections (family ownership) attenuate (strengthen) the monitoring effectiveness of female directors in the corporate board.